Effect of dietary supplementation with vitamin E and stocking density on macrophage recruitment and giant cell formation in the teleost fish, Piaractus mesopotamicus - Belo, M. A A [UNESP]; Schalch, S. H C [UNESP]; Moraes, F. R. [UNESP]; Soares, V. E. [UNESP]; Otoboni, A. M M B [UNESP]; Moraes, J. E R [UNESP] (Elsevier, 2005)
The effect of dietary supplementation with 0, 100 and 450 mg of vitamin E (DL-α tocopheryl acetate)/kg of a dry diet on the kinetics of macrophage recruitment and giant cell formation in the pacu, maintained at different stocking densities (5 kg/m3 and 20 kg/m3), was investigated by insertion of round glass coverslips into the subcutaneous connective tissue. After a feeding period of 18 weeks, the coverslips were implanted and later removed for examination at 2, 7 and 15 days post-implantation. Fish fed diets supplemented with 450 mg of vitamin E showed an increase (P<0.05) in the accumulation of macrophages, foreign body giant cells and Langhans type cells. The kinetics of macrophage recruitment and giant cell formation on the glass coverslips appeared to be strongly influenced by vitamin E supplementation, since fish fed a basal diet and held at high stocking densities showed low numbers of adhering cells on the coverslips, and high concentrations of plasma corticosteroids. On the other hand, fish given a diet supplemented with 450 mg of vitamin E did not show a similar difference in plasma cortisol concentrations related to stocking density. The effect of cortisol concentrations on carbohydrate metabolism, analysed by assessment of plasma glycaemia, was not clear. Blood glucose concentrations did not vary substantially with the different treatments examined. These results suggest that vitamin E may contribute to the efficiency of the fish's inflammatory response by increasing macrophage recruitment and giant cell formation in the foreign body granulomatous reaction. Vitamin E appeared to act on the stress response of pacus by preventing a stress-related immunosuppression. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Alpha-tocopherol; Cortisol; Fish; Piaractus mesopotamicus; Polykaryon macrophage; Vitamin E; alpha tocopherol; corticosteroid; glucose; hydrocortisone; animal cell; animal experiment; carbohydrate metabolism; cell adhesion; cell transport; controlled study; corticosteroid blood level; diet supplementation; feeding; glucose blood level; granulomatosis; hydrocortisone blood level; immunosuppressive treatment; Langhans giant cell; macrophage; nonhuman; oxidative stress; stocking density; teleost; transport kinetics; Animal Husbandry; Animals; Blood Glucose; Cell Count; Cell Movement; Crowding; Diet; Dose-Response Relationship, Drug; Fishes; Foreign-Body Reaction; Giant Cells, Foreign-Body; Hydrocortisone; Langerhans Cells; Macrophages; Population Density; Teleostei